Faithful measures : new methods in the measurement of religion - Finke, Roger, 1954- (New York University Press, 2017)
A venture into the art and science of measuring religion in everyday life In an era of rapid technological advances, the measures and methods used to generate data about religion have undergone remarkably little change. Faithful Measures pushes the study of religion into the 21st century by evaluating new and existing measures of religion and introducing new methods for tapping into religious behaviors and beliefs. This book offers a global and innovative approach, with chapters on the intersection of religion and new technology, such as smart phone apps, Google Ngrams, crowdsourcing data, and Amazon buying networks. It also shows how old methods can be improved by using new technology to create online surveys with experimental designs and by developing new ways of mining data from existing information. Chapter contributors thoroughly explain how to employ these new techniques, and offer fresh insights into understanding the complex topic of religion in modern life. Beyond its quantitative contributions, Faithful Measures will be an invaluable resource for inspiring a new wave of creativity and exploration in our connected world.